2019
DOI: 10.1590/1678-4162-8958
|View full text |Cite
|
Sign up to set email alerts
|

Insecticidal activities and mechanism of extracts from neem leaves against Oxya chinensis

Abstract: In this study, neem leaves were successively extracted with petroleum ether, 95% ethanol and water and the insecticidal activities of these extracts against Oxya chinensis larvae were measured. The results showed that 95% ethanol extract gave the highest extraction yield and insecticidal activity, and it was further extracted with five different solvents. The petroleum ether extract from the 95% ethanol extract possessed the highest insecticidal activity with median lethal concentration values ranging from 14.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 23 publications
0
1
0
Order By: Relevance
“…For example, the use of neem oil against Bemisia tabaci resulted in low mortality in both laboratory assays and field assays [ 11 ]. Li et al [ 12 ] reported the use of neem leaf extracts against Oxya chinensis . The ethanolic extract showed a mortality of 26.67%.…”
Section: Introductionmentioning
confidence: 99%
“…For example, the use of neem oil against Bemisia tabaci resulted in low mortality in both laboratory assays and field assays [ 11 ]. Li et al [ 12 ] reported the use of neem leaf extracts against Oxya chinensis . The ethanolic extract showed a mortality of 26.67%.…”
Section: Introductionmentioning
confidence: 99%